Pengaruh Disiplin Kerja dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada PT Tunggal Djaja Indah - Mardhiyyah, Febriyanti; Endang Iryanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The success and sustainability of an organization can be determined by one of its factors, namely employee performance. Factors related to employee performance such as work discipline and organizational commitment are the problems in this study. The purpose of this study was to determine the effect of work discipline and commitment on employee performance at PT Tunggal Djaja Indah. This research method uses a quantitative approach with SmartPLS analysis techniques. The tests carried out include outer model tests, inner model tests, and hypothesis tests. The number of samples used was 56 employees in the production department of PT Tunggal Djaja Indah. The results of the study showed a significant positive effect of work discipline on employee performance, as well as a significant positive effect of organizational commitment on employee performance.